Effects of the Combination of Honey and Euphorbia hirta on Controlling Aeromonas hydrophila in Catfish (Clarias gariepinus) - Salosso, Yuliana; Rahma, Andi Taufika; Djonu, Asriati; Fransira, Immaria (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Research Highlights The combination of honey and hirta improved hematological parameters of C. gariepinus catfish infected with A. hydrophila bacteria. The combination of honey and hirta positive affected the histopathology of liver, kidneys, and gills, which led to a restoration of organ function to normal levels. The combination of honey and hirta also improved the morphology of C. gariepinus. The most effective combination of honey and hirta was treatment C (1:2). Abstract Honey and Euphorbia hirta are natural ingredients that may serve as alternative treatments for Clarias gariepinus catfish infected with Aeromonas hydrophila bacteria. Both honey and E. hirta contain bioactive compounds with known antibacterial properties. This study aims to investigate the effects of combining honey and E. hirta on various hematological parameters, including erythrocytes, leukocytes, MCH, MCV, as well as histopathological and morphological changes in C. gariepinus catfish infected with A. hydrophila. This study used an experimental design involving three treatment combinations of honey and E. hirta, which were A (2:1), B (1:1), C (1:2) and a control with three replications. The treatments were administered to the fish through immersion. Honey was diluted at a 50% concentration in distilled water. Meanwhile, E. hirta was prepared as a coarse powder and boiled at a 3% concentration. The results showed that the combination of honey and E. hirta affected the hematological, histopathological, and morphological parameters of C. gariepinus catfish within the normal ranges. The most effective treatment was found to be treatment C (1:2). Therefore, the combination of honey and E. hirta is potential as a therapeutic option for bacterial infections in fish.